(untitled) (Nordic Journal of African Studies, 2005)
This study presents a description and analysis of the problems associated with the identification of the internal structure as well as the derivational sources of the Yoruba complex verbs. I attempt the lexical decomposition of these composite forms within the framework of a lexical morphology vis-à-vis my knowledge as a native speaker of the language. I find that some complex verbs have had their forms modified, thereby causing some disturbances in the recognition of their component forms. I also find that a sizeable number of Yoruba verbs are not only complex but are also deemed to be either fossilized or completely opaque to any synchronic analysis. A number of hypotheses about the apparent derivational history and processes of this class of verbs are postulated. In conclusion, I posit that the absence of formal written tradition in the distant past among the Yoruba people, coupled with the paucity of research in the areas of historical linguistics in the language, account for the reasons why some verbs appear recalcitrant and defy systematic morphological analysis.